2014
DOI: 10.3389/fmicb.2014.00531
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and phylogeography of functional genes shared among seven terrestrial subsurface metagenomes reveal N-cycling and microbial evolutionary relationships

Abstract: Comparative studies on community phylogenetics and phylogeography of microorganisms living in extreme environments are rare. Terrestrial subsurface habitats are valuable for studying microbial biogeographical patterns due to their isolation and the restricted dispersal mechanisms. Since the taxonomic identity of a microorganism does not always correspond well with its functional role in a particular community, the use of taxonomic assignments or patterns may give limited inference on how microbial functions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 106 publications
3
73
0
Order By: Relevance
“…DNA extraction and sequencing DNA was extracted from the MNY filter as described in Lau et al, (2014). The DNA sample was sent to the Marine Biological Laboratory (MBL, Woods Hole, MA, USA) for whole-genome library prep using NuGen Ultralow Ovation system that included 18 cycles of PCR amplification of all adaptor-viable molecules (http://nugen.com).…”
Section: Free Energy Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction and sequencing DNA was extracted from the MNY filter as described in Lau et al, (2014). The DNA sample was sent to the Marine Biological Laboratory (MBL, Woods Hole, MA, USA) for whole-genome library prep using NuGen Ultralow Ovation system that included 18 cycles of PCR amplification of all adaptor-viable molecules (http://nugen.com).…”
Section: Free Energy Fluxmentioning
confidence: 99%
“…Samples for cation and anion analysis were collected using the protocols described in Lau et al (2014). Mineral solubility, dissolved species activity, partial pressures and free energy of microbial reactions were calculated using the geochemical modeling program, The Geochemist's Workbench version 8.0 (Bethke, 2008).…”
Section: Free Energy Fluxmentioning
confidence: 99%
“…Analysis of water samples retrieved from ultra-deep South African mines showed the ubiquitous presence of known variants of nitrogen cycling genes such as NarV, NPD, PAPS reductase, NifH, NifD, NifK, NifE, and NifN. Interestingly, the authors found no significant correlation in these samples to geographical or subsurface environmental parameters [61]. …”
Section: Deep Subterranean Habitatsmentioning
confidence: 93%
“…Some key insights into nitrogen cycling processes in subsurface habitats have been gained via the application of metagenome sequencing [61]. Analysis of water samples retrieved from ultra-deep South African mines showed the ubiquitous presence of known variants of nitrogen cycling genes such as NarV, NPD, PAPS reductase, NifH, NifD, NifK, NifE, and NifN.…”
Section: Deep Subterranean Habitatsmentioning
confidence: 99%
“…2) (Stevens and McKinley, 1995;Chapelle et al, 2002;Sleep et al, 2004;Lin et al, 2006;Chivian et al, 2008). A wide diversity of bacteria and archaea has been detected in the continental subsurface, with the majority of these appearing to be indigenous and adapted to subterranean life (Heim, 2011;Colwell and D'Hondt, 2013;Lau et al, 2014). These microbes are active, albeit at slow metabolic rates, and thus are important in the biogeochemical cycling of carbon (Head et al, 2003), nitrogen , and other biologically relevant, redox-sensitive elements .…”
Section: The Deep Biospherementioning
confidence: 99%